2013
DOI: 10.1104/pp.113.232462
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Aspartate and Prephenate Aminotransferase Activities in Plastid Nitrogen Metabolism

Abstract: Chloroplasts and plastids of nonphotosynthetic plant cells contain two aspartate (Asp) aminotransferases: a eukaryotic type (Asp5) and a prokaryotic-type bifunctional enzyme displaying Asp and prephenate aminotransferase activities (PAT). We have identified the entire Asp aminotransferase gene family in Nicotiana benthamiana and isolated and cloned the genes encoding the isoenzymes with plastidic localization: NbAsp5 and NbPAT. Using a virus-induced gene silencing approach, we obtained N. benthamiana plants si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…3). Interestingly, Maeda et al (2011) and Graindorge et al (2010) report that plant prokaryotictype AATs display not only AAT activity but also prephenate aminotransferase activity, which is a key step in the biosynthesis of aromatic amino acids in plastids, a metabolic link between glutamate and phenylpropanoid metabolism (de la Torre et al, 2014).…”
Section: Gs/gogat Gaba and Other Stress Related Compoundsmentioning
confidence: 99%
“…3). Interestingly, Maeda et al (2011) and Graindorge et al (2010) report that plant prokaryotictype AATs display not only AAT activity but also prephenate aminotransferase activity, which is a key step in the biosynthesis of aromatic amino acids in plastids, a metabolic link between glutamate and phenylpropanoid metabolism (de la Torre et al, 2014).…”
Section: Gs/gogat Gaba and Other Stress Related Compoundsmentioning
confidence: 99%
“…Unlike the major effect of ADT suppression on the levels of Phe and Phe-derived compounds (Maeda et al, 2010, Corea et al, 2012a, 2012b, PPA-AT suppression led to a minor reduction in Phe levels (Maeda et al, 2011;de la Torre et al, 2014). However, this was due to compensatory operation of Phe biosynthesis via alternative phenylpyruvate pathway mediated by a separate phenylpyruvate aminotransferase (Yoo et al, 2013), which is homologous to tyrosine aminotransferase and has a broad substrate specificity (Gelfand and Steinberg, 1977;Gonda et al, 2010;Lee and Facchini, 2011;Riewe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, this was due to compensatory operation of Phe biosynthesis via alternative phenylpyruvate pathway mediated by a separate phenylpyruvate aminotransferase (Yoo et al, 2013), which is homologous to tyrosine aminotransferase and has a broad substrate specificity (Gelfand and Steinberg, 1977;Gonda et al, 2010;Lee and Facchini, 2011;Riewe et al, 2012). Thus, besides having a role in plastidic aspartate metabolism owing to its Asp-AT activity (de la Torre et al, 2014), the identified plant PPA-ATs are indeed involved in Phe biosynthesis (Maeda et al, 2011;Yoo et al, 2013;de la Torre et al, 2014). The strict substrate specificity of plant PPA-ATs toward prephenate among the three aromatic keto acid substrates in Phe and Tyr biosynthesis (Graindorge et al, 2010;Maeda et al, 2011) also suggest that plant PPA-AT directs carbon flow specifically from prephenate toward arogenate and hence serves as an ideal marker to investigate the molecular and biochemical evolution of the plant arogenate pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin levels were determined by the thioacidolysis method [35] and adapted as previously described [36]. …”
Section: Methodsmentioning
confidence: 99%